2012
DOI: 10.1159/000336722
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Appraisal of Endoscopy with Narrow-Band Imaging System in the Evaluation and Management of Homogeneous Oral Leukoplakia

Abstract: <i>Purpose:</i> To evaluate the clinical usefulness of endoscopy with a narrow-band imaging (NBI) system for the evaluation and management of homogeneous oral leukoplakia. <i>Methods:</i> The chart records, morphology of vascular architecture of NBI, and histopathology of patients with homogeneous leukoplakia were retrospectively reviewed and analyzed. <i>Results:</i> A total of 160 patients, with an average age of 50.96 ± 10.25 years, were enrolled. In 35 cases of thin leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 42 publications
0
32
0
Order By: Relevance
“…Type IV IPCL pattern, however, is indicative of neoplasia [65] and is characterised by large vessels IPCL pattern destruction and angiogenesis (Figure 3) [61]. Any lesion with Types III and IV should therefore be biopsied [67], particularly since the use of Types III and IV as the criteria for differentiating high-grade dysplasia, CIS, and invasive carcinoma from normal mucosa has been shown to have 85% sensitivity, 95% specificity, 74% positive predictive value (PPV), 97% negative predictive value (NPV), and 93% accuracy (Table 3) [65]. …”
Section: Narrow Band Imagingmentioning
confidence: 99%
See 3 more Smart Citations
“…Type IV IPCL pattern, however, is indicative of neoplasia [65] and is characterised by large vessels IPCL pattern destruction and angiogenesis (Figure 3) [61]. Any lesion with Types III and IV should therefore be biopsied [67], particularly since the use of Types III and IV as the criteria for differentiating high-grade dysplasia, CIS, and invasive carcinoma from normal mucosa has been shown to have 85% sensitivity, 95% specificity, 74% positive predictive value (PPV), 97% negative predictive value (NPV), and 93% accuracy (Table 3) [65]. …”
Section: Narrow Band Imagingmentioning
confidence: 99%
“…A study by Lin et al [70] found that areas with nonkeratinized thin stratified squamous epithelium had a significantly higher prevalence of brownish spots than areas with keratinized epithelium or epithelium thicker than 500  μ m. However, Yang et al [65] reported that the degree of keratinization did not affect visualisation of the underlying vasculature unless hyperkeratosis associated with leukoplakia was present. Visualisation of the microvasculature is possible through thin homogenous leukoplakia, but the vasculature will appear vague, blurry, or be completely obstructed where there is thick homogenous leukoplakia [67]. In the latter case, the IPCL pattern of the surrounding mucosa is often observed to guide the determination of the lesion's IPCL class; however, this is not completely reliable as one study [67] found dysplasia in 28% of thick homogenous leukoplakia surrounded by IPCL Type I.…”
Section: Narrow Band Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…NBI is an imaging technique that accentuates abnormalities in the superficial vasculature of mucosal lesions by using narrow‐bandwidth filters in a sequential red/green‐blue illumination system. NBI, which is used in both flexible and rigid endoscopes, is now established as an important tool in the detection of various head and neck tumors and is helpful in differentiating malignant from benign lesions . Since the first studies with NBI by Muto et al, the number of NBI studies in head and neck cancer has been growing rapidly.…”
Section: Introductionmentioning
confidence: 99%